(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Water is poised to become the most critical natural resource of the third millennium, influencing both economic stability and human survival, particularly as developing nations face rapid population growth. This surge in population and industrial activity is driving up water demand while simultaneously depleting available resources. The resulting gap between high demand and dwindling supply poses significant challenges for water distribution. This study outlines a methodology for forecasting population growth and water demand in the Denpasar area over a ten-year period. Three projection models—linear, quadratic, and exponential—were evaluated to identify the most accurate solution. The findings indicate that the quadratic method provides the most reliable forecast for Denpasar's future water needs. Current projections reveal that existing water infrastructure can only meet 41.63% of total demand. Consequently, it is imperative for the Denpasar municipal government to implement more robust strategies to address this substantial supply deficit